Docência na educação infantil durante a pandemia da Covid-19: investigação-formação em ambiências bioecológicas - Berleze, Eliana Avinio (2022)
This dissertation is part of the LP2 research line, entitled: Gestão Pedagógica e Contextos Educativos, of the Programa de Pós-Graduação em Políticas Públicas e Gestão Educacional, Mestrado Profissional em Políticas Públicas e Gestão Educacional, of the Universidade Federal de Santa Maria (UFSM). It presents as a theme the sustainable bio-ecological environments in the context of teaching during the pandemic of COVID 19, considering the perspectives of the teachers of a municipal public school in Santa Maria-RS. It presents a research problem: To what extent did the remote experiences build new knowledge and doings during the pandemic of COVID - 19, considering the perspectives of teachers of a municipal public school of Campo preschool? As a general research objective: To understand how remote experiences have constructed new knowledge and doings during the pandemic of COVID 19, considering the teachers' perspectives in a municipal school of Campo Infantil Education. The proposed methodology is characterized as a qualitative study, considering the methodology of Research-Training in Reflective Group (MACIEL, 2006) and the PPCT Model, by Urie Bronfenbrenner. The theoretical basis brings the studies of Urie Bronfenbrenner, with the Bioecological Theory of Human Development, Malaguzzi (1999, 2005) and Barbosa (2009) with the concept of childhood school, Maciel and Avinio (2019) with the concept of ambiance. This dissertation it is intended to reflect and qualify teaching practices, contributing to the improvement of Early Childhood Education.